Identification of genes involved in flowering in Stevia rebaudiana using expressed sequence tags (ESTs) - Razali, Amin; Samsulrizal, Nurul Hidayah; Zainuddin, Zarina (University of Malaya, 2020)
tevia rebaudiana, or stevia, is a perennial herb native to the northern region of South America. It is commercially important due to the high level of non-caloric sweetening compound, which has been consumed worldwide as food and medicine. Stevioside is considered as the most important compound of steviol glycosides that functions as the main sweetener. Exposure of the stevia plant to long-day conditions (increased exposure to light) will delay the flowering process, which led to an increase in glycoside accumulation. The bioinformatics analysis of 5548 expressed sequence tags (ESTs) obtained from dbEST (NCBI) using the Blast2GO software and manual curation identified 7 ESTs that contain domains involved in the flowering process. The domains were the heat shock protein (Hsp) domain, squamosa promoter-binding protein (SBP) domain, CONSTANS, CO-like, and TOC1 (CCT) domains; K homology (KH) domain; and ubiquitin-conjugating enzyme domain (UBC).